2005
DOI: 10.1161/circulationaha.105.551648
|View full text |Cite
|
Sign up to set email alerts
|

Preprocedural Levels of C-Reactive Protein and Leukocyte Counts Predict 9-Month Mortality After Coronary Angioplasty for the Treatment of Unprotected Left Main Coronary Artery Stenosis

Abstract: Background-An accurate preprocedural risk stratification scheme for patients with unprotected left main coronary artery (ULMCA) stenosis who are undergoing coronary stenting is lacking. We examined the predictive value of preprocedural levels of C-reactive protein (CRP), fibrinogen, and leukocyte counts with respect to 9-month clinical outcomes after stenting of the ULMCA stenosis. Methods and Results-Levels of CRP, fibrinogen, and leukocyte count were prospectively measured in 83 patients undergoing stenting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 35 publications
3
33
0
Order By: Relevance
“…Recent observational studies suggested that periprocedural CRP levels might be a risk indicator for clinical outcomes after DES implantation. 20,21 However, these studies were hampered by small patient numbers, limited durations of follow-up, or a retrospective observational study design. The present study highlights the prognostic value and clinical usefulness of CRP among patients treated with DES in several important respects.…”
Section: Discussionmentioning
confidence: 99%
“…Recent observational studies suggested that periprocedural CRP levels might be a risk indicator for clinical outcomes after DES implantation. 20,21 However, these studies were hampered by small patient numbers, limited durations of follow-up, or a retrospective observational study design. The present study highlights the prognostic value and clinical usefulness of CRP among patients treated with DES in several important respects.…”
Section: Discussionmentioning
confidence: 99%
“…40-42 Furthermore, one study has shown that the serum level of high-sensitivity C-reactive protein may independently predict 9-month mortality following after PCI for ULMCA stenosis. 43 Therefore, the association between TLR and significant HF needs to be verified in a large-scale study.…”
Section: Hf and Outcomes Following Pci For Distal Ulmca Stenosismentioning
confidence: 99%
“…Although vascular trauma from PCI denudes endothelium and initiates vascular wound healing with early inflammation and smooth muscle cell proliferation, there is generally a reduction in systemic markers of inflammation after PCI. 19 Genetic analyses suggest markers for increased risk of restenosis. The improved blood flow and reduced stasis at sites where stenosis is removed also may reduce the intense inflammation seen in unstable plaque before intervention, but this remains speculative.…”
Section: Pci and Coated Stent Implantsmentioning
confidence: 99%